A study of the social stigma of coronavirus (COVID-19) - Naeim , Mahdi (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Infectious disease disasters, including epidemics, pandemics, and outbreaks, may cause high morbidity and mortality and may account for 1/4 to 1/3 of the worldwide death rate [1]. For the past 2 months, the difficulty of the new virus (COVID-19) and its spread to other parts of the globe after/since the outbreak in Wuhan, China, has been the most focus of healthcare providers around the world [2]. The new Coronavirus (COVID-19) may be a new sort of family that didn't exist before in humans. Coronaviruses are zoonotic, meaning they're also trans-mitted from animals to humans. Common symptoms of the new virus include respiratory symptoms, cough, shortness of breath, fever. In additional severe cases, the infection can cause pneumonia, renal failure, severe acute respiratory syndrome, and even death [3]. COVID-19 was first reported on, 2019, in Wuhan, China.